KEPEMIMPINAN KEPALA UNIT PELAKSANA TEKNIS (UPT) PENDIDIKAN KECAMATAN DALAM IMPLEMENTASI KEBIJAKAN PENDIDIKAN NONFORMAL DI KABUPATEN BANJAR - Sumadi Sumadi (Jurnal Good Governance, 2018)
District Education Technical Implementation Unit (UPT) having duties and functions includes providing guidance to PAUD education units and non-formal education. In an effort to realize the vision, mission, and goals of education, as well as an increase in the average number of years of schooling in Banjar district, an important role of the Head of the UPT is needed. District education, namely: (1) interpersonal roles, informational roles, role of decision makers, and the role of supervision in the implementation of non-formal education policies. The purpose of this study in detail is to describe and explain: (1) the role of interpersonal (2) informational role, (3) the role of decision maker (decision maker), (4) the role of controlling the head of the UPT. Education in Martapura, Astambul, and Mataraman Districts in the implementation of non-formal education policies. This study uses a qualitative approach to naturalistic phenomenology, with a multi-case study study design using in-depth interview techniques, observation, and documentation studies, holistic data analysis, and reporting by describing themes, issues, and implications of the phenomenon between cases contextually. The results showed that: (1) The role of interpersonal head of the UPT. Martapura District Education, UPT. Astambul Education, and UPT. Mataraman District education in the implementation of non-formal education policies tends to be persuasive, participatory, and motivational styles in the implementation of non-formal education policies. (2) Informational roles tend to delegate to staff, and those who are trusted in receiving, sharing and monitoring information, are focused on the leadership in receiving, sharing, and monitoring information, and adjusting the situation and conditions as well as the substance of information (delegation or centralization to the leadership). (3) Role of Decision Makers leaders tend towards democratic, participatory and situational types. (4) The role of supervision carried out by leaders varies according to scheduled, unscheduled, scheduled but tentative adjusting needs, oriented to the process and results in supporting the implementation of non-formal education policies. Suggestions are addressed to: (1) UPT. District Education in the Banjar Regency region, the results of this study can provide a positive contribution to the increasing role of the Head of the UPT. Education from the perspective of leadership management, (2) the Education Office of Banjar Regency as the Development Agency, the results of this study can provide input as a policy direction, (3) Human Resources Development Agency (BPSDM) of South Kalimantan Province as a reference for the development and improvement of human resources leadership and as a reference in adding repertoire to further research.Keywords: Role of Leadership, Policy Implementation, Non-formal Education